2014
DOI: 10.7554/elife.02362
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of HIV-1 Vpu-mediated BST2 antagonism via hijacking of the clathrin adaptor protein complex 1

Abstract: BST2/tetherin, an antiviral restriction factor, inhibits the release of enveloped viruses from the cell surface. Human immunodeficiency virus-1 (HIV-1) antagonizes BST2 through viral protein u (Vpu), which downregulates BST2 from the cell surface. We report the crystal structure of a protein complex containing Vpu and BST2 cytoplasmic domains and the core of the clathrin adaptor protein complex 1 (AP1). This, together with our biochemical and functional validations, reveals how Vpu hijacks the AP1-dependent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 95 publications
10
138
2
Order By: Relevance
“…Another possibility is that the C-terminal membrane attachment correctly orients the cytoplasmic domain of Vpu such that it can interact with a cellular peripheral membrane or cytoskeletal protein, and this connection ultimately provides the movement of BST2 relative to viral assembly sites. Such a co-factor might, for example, be a clathrin adaptor, an hypothesis consistent with the role reported for the EXXXLV 64 adaptor protein binding sequence in the displacement effect (16,42). In either case, Vpu would presumably need to interact with BST2 at assembly sites initially, and then move together with BST2 away from those sites.…”
Section: Discussionmentioning
confidence: 55%
“…Another possibility is that the C-terminal membrane attachment correctly orients the cytoplasmic domain of Vpu such that it can interact with a cellular peripheral membrane or cytoskeletal protein, and this connection ultimately provides the movement of BST2 relative to viral assembly sites. Such a co-factor might, for example, be a clathrin adaptor, an hypothesis consistent with the role reported for the EXXXLV 64 adaptor protein binding sequence in the displacement effect (16,42). In either case, Vpu would presumably need to interact with BST2 at assembly sites initially, and then move together with BST2 away from those sites.…”
Section: Discussionmentioning
confidence: 55%
“…Bst2 has also been shown to activate the NF-B pathway, presumably further amplifying cellular stress signals (17). While the functional roles of Bst2 in uninfected cells are just emerging, it is clear that many viruses encode proteins that subvert Bst2's antiviral activities, often by altering clathrin-mediated endocytic pathways (18)(19)(20). To date, studies aimed at understanding Bst2's role in preventing viral infection have been limited Citation Holmgren AM, Miller KD, Cavanaugh SE, Rall GF.…”
mentioning
confidence: 99%
“…It has been shown that human tetherin (also termed BST2) interacts with Vpu (456)(457)(458)(459)(460)(461)(462)(463) and Nef (464). Meanwhile, CD4 physically binds to Vpu (14,19,433) and Nef (465).…”
Section: Vpu-tetherin/cd4-nef Associationmentioning
confidence: 99%
“…Different aspects of this mechanism have been reported. (i) HIV-1 Vpu hijacks trafficking pathways of the clathrin adaptor protein complex 1 (AP1) and adaptor protein complex 2 (AP2) to induce postendocytic membrane trafficking events that remove tetherin from the cell membrane (456,458). (ii) Despite the fact that tetherin enhances the susceptibility of HIV-infected cells to antibodies, HIV-1 Vpu and Nef antagonize tetherin to protect HIV-infected cells from antibody-dependent cell-mediated cytotoxicity, a type of human immune response where virus-specific antibodies activate the killing of HIV-infected cells (470)(471)(472).…”
Section: Vpu-tetherin/cd4-nef Associationmentioning
confidence: 99%